Il centro nazionale per il futuro della biodiversità e le sfide della biodiversità: ricerca, comunicazione e sensibilizzazione. Intervista a Gianluca Sarà (Itinera, 2025)
The national biodiversity future centre and the challenges of biodiversity: research, communication and awareness raising. Interview with Gianluca SaràThis interview with Gianluca Sarà - Professor of Ecology, head of the Ecology Laboratory (EEB) at the Earth and Marine Sciences Department (DISTEM) of Palermo University (Italy) and head of Spoke 1 of the National Biodiversity Future Centre (NFBC) - aims to provide an overview of the National Biodiversity Future Centre, the first National Research and Innovation Centre dedicated to biodiversity, funded by the MUR through European Union funds - NextGenerationEU. An ambitious project that combines science, technology and applied research and brings together researchers from universities, research centres and companies throughout Italy, from scientific disciplines that are apparently very distant from each other, with the conviction that the diversity of theoretical approaches is an asset for investigating biodiversity. The interview aims to highlight the role that aesthetics and the arts can play in promoting not only more effective communication of scientific research on biodiversity to the general public, but also (and perhaps above all) in raising awareness of the dangers of increasing biodiversity loss, appealing to languages and practices other than those of science.
Keywords: Biodiversity; NFBC; Aesthetics of Biodiversity; art languages